Hubungan Parent Attachment dan Peer Social Support dengan Self-Esteem pada Siswa SMA X Pekanbaru: Hubungan Parent Attachment dan Peer Social Support dengan Self-Esteem pada Siswa SMA X Pekanbaru - Nurjana, Siti; Hirmaningsih (Persepsi: Jurnal Riset Mahasiswa Psikologi, 2024)
The High School period is a transition period to college. High school students as a teenager tend to experience a decrease in self-esteem or also called self-esteem. Self-esteem is how individuals evaluate themselves and feel that they are valuable. Important factors in the development of self-esteem in adolescence are parent attachment and peer social support. So this study seeks to examine how the relationship between parent attachment and peer social support on adolescent self-esteem at SMA in Pekanbaru. A total of 199 samples have participated to measure personality characteristics. Non-parametric analysis was used to see the relationship between parent attachment and peer social support with self-esteem at SMA in Pekanbaru students. This study shows that parent attachment and peer social support have a positive relationship with adolescent self-esteem at SMA in Pekanbaru. Keywords: self-esteem, parent attachment, peer social support.